2016
DOI: 10.1155/2016/2526789
|View full text |Cite
|
Sign up to set email alerts
|

Needle Fracture during Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Suspicious Thoracic Lymph Nodes

Abstract: Endoscopic ultrasound fine-needle aspiration (EUS-FNA) is used to make a cytopathologic diagnosis of suspicious lesions located around the gastrointestinal tract. It is a safe technique with few complications. The most common complications of EUS-FNA are related to pancreatic lesions (pancreatitis, bleeding, and abdominal pain). Rare complications have been noted such as stent malfunction, air embolism, infection, neural and vascular injuries, and tumor cell seeding. There are very few studies examining equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…There are limited reports describing needle fracture as a complication during EUS-FNA. Adamowicz et al reported needle fracture during EUS-FNA of suspicious thoracic lymph nodes 5 . A 22-gauge needle without a side hole was used to puncture the rigid lymph node from the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited reports describing needle fracture as a complication during EUS-FNA. Adamowicz et al reported needle fracture during EUS-FNA of suspicious thoracic lymph nodes 5 . A 22-gauge needle without a side hole was used to puncture the rigid lymph node from the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported similar experience as described in [ Supplementary Table 1 ]. [ 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ] A nationwide survey by the Japan Society for Respiratory Endoscopy focused on complications associated with EBUS-TBNA aspiration and reported the breakage of the puncture needle in 15 (0.20%) cases. [ 4 ] The details of this complication were not described although reported for first time.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of needle tip breakage was reported in detail by Özgül et al .,[ 10 ] followed by other reports. [ 11 12 13 14 15 16 17 18 19 20 ] The retrieval of the broken fragment of EBUS needle by flexible bronchoscopy was successfully reported in most of these cases. [ 11 12 14 16 18 19 20 ] Unsuccessful attempts were also reported where fragments migrated to dependent lobes of lung which were expelled by spontaneous coughing[ 8 13 17 ] or migrated to gastrointestinal tract followed by expulsion in faeces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] hypothesized that this complication may be related to lymph node stiffness. Certain endoscopic maneuvers as torquing, multiple punctures, fanning in a hard lymph node, and hitting the cartilage could all be predisposing factors,[278] which should be as far as possible avoided.…”
mentioning
confidence: 99%